2016
DOI: 10.1371/journal.pone.0159774
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Climate Change Public Opinion in Canada

Abstract: While climate scientists have developed high resolution data sets on the distribution of climate risks, we still lack comparable data on the local distribution of public climate change opinions. This paper provides the first effort to estimate local climate and energy opinion variability outside the United States. Using a multi-level regression and post-stratification (MRP) approach, we estimate opinion in federal electoral districts and provinces. We demonstrate that a majority of the Canadian public consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 23 publications
7
41
0
Order By: Relevance
“…In their landmark study on "Global Warming's Six Americas", Leiserowitz et al found that among the six categories of audiences in the American public -alarmed, concerned, cautious, disengaged, doubtful, and dismissive -belief in the reality of global warming and worry about the impacts were highest among the 'alarmed' and lowest among the 'dismissive' [62]. The results here also indicate more skepticism and denial in rural areas as compared to urban, which aligns with existing data on climate opinions in the region [42]. Humanity's role in causing climate change was debated in Morden and Brandon groups, where survey data indicates that only about half the population in the regions -45% and 51% respectivelybelieve that the earth is warming partly or mostly because of human activity, compared to 60% nationally [42].…”
Section: Key Findingssupporting
confidence: 86%
See 3 more Smart Citations
“…In their landmark study on "Global Warming's Six Americas", Leiserowitz et al found that among the six categories of audiences in the American public -alarmed, concerned, cautious, disengaged, doubtful, and dismissive -belief in the reality of global warming and worry about the impacts were highest among the 'alarmed' and lowest among the 'dismissive' [62]. The results here also indicate more skepticism and denial in rural areas as compared to urban, which aligns with existing data on climate opinions in the region [42]. Humanity's role in causing climate change was debated in Morden and Brandon groups, where survey data indicates that only about half the population in the regions -45% and 51% respectivelybelieve that the earth is warming partly or mostly because of human activity, compared to 60% nationally [42].…”
Section: Key Findingssupporting
confidence: 86%
“…Although high-resolution public opinion data on climate change in Canada is limited, research has shown that discourse and perceptions of climate change in the Prairies are unique compared to other parts of Canada. At the national level, rural areas and Prairie provinces have a high level of climate skepticism and denial [42]. An estimated 42%, 47%, and 57% of people in Alberta, Saskatchewan, and Manitoba respectively, believe that the earth is warming partly or mostly because of human activity, compared to the national average of 60% [42].…”
Section: Study Area and Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased risks of natural hazards will influence how provincial and territorial governments, and municipalities invest in mitigation, adaptation, and relief measures (e.g., Hurlbert and Gupta 2016;Hope et al 2016;Lemprière et al 2017). Divergent societal views on ways to cope with atmospheric change (e.g., Tyrrell 2006;Mantyka-Pringle et al 2015;Mildenberger et al 2016) could yield opportunities to co-operate, or breed tensions across the boreal. The projected spread of climate-sensitive infectious diseases (see Berry et al 2014) and immigration will likely increase the need for economic, social, and health infrastructure.…”
Section: Governance and Geopoliticsmentioning
confidence: 99%